Effects of hypoxia on benthic eggs of calanoid copepods in the Southern Sea of Korea - Choi, Seo Yeol; Soh, Ho Young; Shin, Kyoungsoon; Jung, Seung Won; Jang, Min-Chul (Frontiers in Marine Science, 2023)
Global warming is affecting the composition, structure, and function of marine ecosystems. The increase in hypoxic regions due to stratification is a major environmental problem worldwide. Off the southern coast of Korea, hypoxia occurs frequently in summer, and the area of water affected is gradually expanding. In this study, we investigated the effects of hypoxia on the eggs of copepods in the order Calanoida. Data on the distribution and abundance of eggs in benthic sediments were collected from 17 stations, using a piston core sampler (64 mm internal diameter, 50 cm length), from August 1 to 7, 2012. Significant variations in the distribution of calanoid eggs and the occurrence of abnormalities in egg development were found between stations. The abundance of eggs found in the sediments ranged from 0.004 to 2.389 × 106 eggs·m−2, with higher abundances identified in hypoxic than in normoxic areas. The proportion of abnormal eggs ranged from 0 to 92.7%. In particular, there were significantly more abnormal than normal eggs in areas where hypoxia occurred (p < 0.01). These results show that hypoxia can have a lethal effect on calanoid eggs and further affect population and community dynamics.